A technotypological analysis of the Ahmarian and Levantine Aurignacian assemblages from Manot Cave (area C) and the interrelation with site formation processes. Issue 160 (November 2021) - Abulafia, T.; Goder-Goldberger, M.; Berna, F.; Barzilai, O.; Marder, O.
Abstract: For more than a century, prehistoric research has focused on cave sites and rock shelters, mostly because of good preservation of organic remains associated with stratified anthropogenic layers. Manot Cave in the Western Galilee, Israel offers the possibility of studying prehistoric assemblages in pristine condition because of the collapse of the cave entrance some 30 thousand years ago. Nine years of excavations have uncovered an Early Upper Paleolithic archaeological sequence. Area C, situated at the bottom of the talus, was exposed to fast and slow depositional and postdepositional processes affecting sediment accumulation. The central part of area C was selected for this study, as it was least disturbed. Following a technotypological analysis, and taking postdepositional processes into consideration, the assemblages were defined and assigned to the Levantine Aurignacian, and Ahmarian traditions. The two archaeological horizons are separated by a mixed horizon within which indicative artifacts of both traditions alternately appear. The Ahmarian assemblage, dated to 46–42 ka cal BP, fits within the northern Mediterranean Ahmarian sites, which technotypologically differs from and is currently dated earlier than the southern desert region Ahmarian sites. The main technotypological characteristics of the assemblage from the Levantine Aurignacian Horizon, dated to 38–34 ka cal BP, are comparable to those from Manot Cave area E layers V-VI, and Ksâr 'Akil levels VII-VIII. Yet, several technotypological elements seem more compatible with the unnamed assemblage from Ksâr 'Akil levels XI-XIII and possibly layer IX from area E.